PHYSICO-GEOGRAPHICAL OBSERVATIONS OF THE COASTAL ZONE OF THE NORTHEASTERN PART OF ISLAND RHODES - Βερυκίου-Παπασπυριδάκου Ε.; Μπαθρέλλος Γ.; Σκυλοδήμου Χ. (Bulletin of the Geological Society of Greece, 2018)
Rhodes is the biggest island of the Dodecanese complex; its geology is very interesting for the researchers because it h located onto the eastern end of the Aegean arcade. This paper involves the physico-geographical features of the coastal zone of the NE part of Rhodes. Specifically, the major geological formations of the region were studied and classified, according to their morphology and lithology. In addition, the human interventions that have affected the region were also recorded. The geological formations met in the study region are the following: Mesozoic limestones, Oligocene flysch, Pliocene - Pleistocene marls, calcarenites, and Holocene deposits. Steep slopes and cliffs basically characterize the limestone coasts. Some mirror faults, indicate the intense tectonic movements whereas, some coastlines witness the former sea level. The flysch coasts have mainly steep slope. The coasts, which are developed on marls and calcarenites have got various morphological slopes. This has resulted to the formation of steep costs with cliffs and middle slope costs that are characterized by smooth relief. The coasts developed onto alluvial deposits have mainly gentle slope bearing the bulk of the beaches. They are featured by several geoforms such as coastal dunes, while the human intervention is significant.